Current Molecular Targeted Therapy in Advanced Gastric Cancer: A Comprehensive Review of Therapeutic Mechanism, Clinical Trials, and Practical Application - Kaichun Li; Jin Li (Gastroenterology Research and Practice)
Despite the great progress in the treatment of gastric cancer, it is still the third leading cause of cancer death worldwide. Patients often miss the opportunity for a surgical cure, because the cancer has already developed into advanced cancer when identified. Compared to best supportive care, chemotherapy can improve quality of life and prolong survival time, but the overall survival is often short. Due to the molecular study of gastric cancer, new molecular targeted drugs have entered the clinical use. Trastuzumab, an antibody targeting human epidermal growth factor receptor 2 (HER2), can significantly improve survival in advanced gastric cancer patients with HER2 overexpression. Second-line treatment of advanced gastric cancer with ramucirumab, an antibody targeting VEGFR-2, alone or in combination with paclitaxel, has been proved to provide a beneficial effect. The VEGFR-2 tyrosine kinase inhibitor, apatinib, can improve the survival of advanced gastric cancer patients after second-line chemotherapy failure. Unfortunately, none of the EGFR targeting antibodies (cetuximab or panitumumab), VEGF targeting monoclonal antibodies (bevacizumab), mTOR inhibitor (everolimus), or HGF/MET pathway targeting drugs has a significant survival benefit. Many other clinical trials based on molecular markers are underway. This review will summarize targeted therapies for advanced gastric cancer.